Antistatic composite coatings for protecting magnesium alloys based on powder paints processed in a planetary ball mill - Sergey Yazykov; Vladislav Dammer; Sergey Panin; Boris Ovechkin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The authors have studied possibility of providing electrical conductivity properties to the coating based on powder paints by processing in a planetary ball mill. Changing the duration the mechanical activation as well as the weight fraction of the filler, the properties of powder mixtures were investigated as well as a structure and properties of coatings which functionality is achieved by adding the conductive filler into powder paint and their subsequent joint treatment in planetary ball mill. The main aim of the study is to optimize the structure and properties of composite coatings while keeping initial physical and mechanical properties of powder paint and providing novel functional ones. The methods used in the study. Processing of powder mixtures was carried out by employing planetary ball mill MP 4/0,5 (Technocenter ltd., Rybinsk) with the total frequency of steel bowls rotation of 800 rpm. Carbon black and powder paint in necessary weigh fractions were loaded into the bawls where their joint mechanical activation took place for 20...80 minutes with increment of the treatment time of 10 min. Mechanical activation time influence on powder mixture properties was evaluated by packing density measurement data. The results. During the complex tests it was found that a designed mixture with the weight fraction of carbon black of 12,5 wt. % and the time of the mechanical activation in the planetary ball mill of 40 minutes provides the formation of a coating film with the thickness of 70 mμm having satisfactory functional and protective properties. It is shown that the proposed method of deposition functional coating on the parts of magnesium alloys including adding of conductive filler, powder mixture treatment in the planetary ball mill and electrostatic spraying, may be used to sink static electricity from the spacecraft bodies operating in open space.